Early mathematical experiences: the importance of curricular integration - Ana Barbosa; Isabel Vale (European Teacher Education Network, 2014)
In this paper we explore the implications of some tasks that promote integrated activities in a preschool context. In early years education, children should have meaningful experiences, involving discovery, experimenting and solving challenging problems, based on their interests. All of this should be regarded in an articulated way, intertwining contents, knowledge and processes from different areas. Our main goal is to explore the potential of this approach from were mathematics stands, perceiving the kind of mathematics pre-schoolers should learn, operationalizing it through different types of connections.